The idea of civilization in ancient Indian literature and South Asian archaeology - Eltsov, Peter A. (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
This article focusses on the historical and archaeological value of ancient Indian literature. Besides developing a new method of using Sanskrit and Pãli texts in the reconstruction of South Asian past, the article provides a concrete example of how one historical narrative can alter our understanding of the birth of civilisation on the South Asian Subcontinent. The key theoretical presumption formulated in the beginning of the article lies within the simple fact that history is not just about writing chronicles or tracing l’histoire événementielle, for which ancient Indian literature has clearly very little to offer, but rather about grasping the illusory longue durée, discerning structures and writing analytical narratives, for which ancient Indian literature has much more to offer. Consequently, instead of treating ancient Sanskrit and Pãli texts merely as sources of tedious factual information, it is suggested that we treat them as sources of sociocultural ideas, which can be tested and conceptualised in the context of archaeological data. Epistemologically, this method as presented is part of the author’s broader research philosophy, aimed at combining the efforts of anthropology, archaeology, history and philology and contingent on four rules of thumb: fi rst, that human agency is the main driving force beyond history; second, that the creation of structures and models is essential for the conceptualization of the human past; third, that there can be no purely objective interpretation of the past; and most importantly, fourth, that the ideas and thoughts of historical agents present an intrinsic part of the events, phenomena, processes, structures and models of the past. To substantiate this method with concrete data, a new interpretation of the Yuga Story in the rendition of the Vãyu and Brahmãnda Purãnas is proposed. It is argued that this rendition contains an elaborate model of cultural evolution and incorporates two concepts which are highly reminiscent of the idea of civilization in recent historical and anthropological literature. Based on the analysis and interpretation of these concepts, a new hypothetical model of the ancient Indian civilization is formulated. According to this model, the ethos of the ancient Indian civilization began to form during the Neolithic and Chalcolithic periods and was defi ned by five traits – agricultural economy, orally transmitted ethical and legal norms, orally transmitted sacred knowledge, an idiosyncratic semi-hierarchical / semi-heterarchical social system, and a set of ritual and sacrifi cial practices. Meanwhile, cities, writing, monumental architecture and other traits that for a long time have been seen as the defi nitive markers of civilization are epiphenomenal to the ethos of ancient India.The article will be available as a PDF in the near future.